2009
DOI: 10.1029/2009gl040348
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐seasonal variability of polar mesospheric clouds due to inter‐hemispheric coupling

Abstract: [1] Polar mesospheric cloud (PMC) observations have revealed that interannual variability near the polar summer mesopause can be forced by planetary wave activity in the winter stratosphere. We use data from the Aeronomy of Ice in the Mesosphere (AIM) satellite to investigate coupling between the Arctic winter stratosphere and PMC variability in the Antarctic summer of 2007 -2008. We find a high correlation between zonal mean PMC frequency and Arctic winter zonal mean winds from the Goddard Earth Observing Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
61
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 16 publications
12
61
2
Order By: Relevance
“…Thus we saw an 8% decrease in the frequency of occurrence in clouds seen in solar occultation by SOFIE near 681N, a factor of two decrease in the ice water content observed by SOFIE and a factor of 5-6 in the number of clouds seen by SHIMMER at sub-arctic latitudes. The 2007 PMC reductions are seen to be linked to SH winter weather as first postulated by Becker et al (2004) and discussed by Karlsson et al (2007Karlsson et al ( , 2009b. This is consistent with earlier reports of such inter-hemispheric teleconnections; our results are the first to use a global analysis of the stratosphere and mesosphere with a cloud formation model to document these effects.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus we saw an 8% decrease in the frequency of occurrence in clouds seen in solar occultation by SOFIE near 681N, a factor of two decrease in the ice water content observed by SOFIE and a factor of 5-6 in the number of clouds seen by SHIMMER at sub-arctic latitudes. The 2007 PMC reductions are seen to be linked to SH winter weather as first postulated by Becker et al (2004) and discussed by Karlsson et al (2007Karlsson et al ( , 2009b. This is consistent with earlier reports of such inter-hemispheric teleconnections; our results are the first to use a global analysis of the stratosphere and mesosphere with a cloud formation model to document these effects.…”
Section: Discussionsupporting
confidence: 79%
“…Subsequent work by Karlsson et al (2007Karlsson et al ( , 2009aKarlsson et al ( and 2009b) have shown that these long range teleconnections between the winter in one hemisphere and the summer in the other occur quite often. This effect can be documented for both interannual variability as well as within a single season.…”
Section: Introductionmentioning
confidence: 99%
“…Becker and Fritts, 2006). Karlsson et al (2009b) observed the effect of this increased summer mesopause temperature in relation to strong winter stratosphere PW activity as well, using polar mesospheric cloud occurrence frequency as a proxy for polar mesopause temperature. However, as this technique can only determine temperature changes in a thin layer, no vertical profiles were shown.…”
Section: Discussionmentioning
confidence: 99%
“…This shift represents a typical response time of the summer mesosphere to influences from the winter stratosphere. The underlying wave interactions and propagation times have been discussed by Karlsson et al [2009a] and Körnich and Becker [2010].…”
Section: Discussionmentioning
confidence: 99%